Absence of CD36 alters systemic vitamin A homeostasis - Michael J. Trites (Nature Portfolio, 2020)
Abstract Fatty acid translocase (CD36) is a scavenger receptor with multiple ligands and diverse physiological actions. We recently reported that alcohol-induced hepatic retinoid mobilization is impaired in Cd36 −/− mice, leading us to hypothesize that CD36 has a novel role in hepatic vitamin A mobilization. Given the central role of the liver in systemic vitamin A homeostasis we also postulated that absence of CD36 would affect whole-body vitamin A homeostasis. We tested this hypothesis in aging wild type and Cd36 −/− mice, as well as mice fed a vitamin A-deficient diet. In agreement with our hypothesis, Cd36 −/− mice accumulated hepatic retinyl ester stores with age to a greater extent than wild type mice. However, contrary to expectations, Cd36 −/− mice consuming a vitamin A-deficient diet mobilized hepatic retinoid similar to wild type mice. Interestingly, we observed that Cd36 −/− mice had significantly reduced white adipose tissue retinoid levels compared to wild type mice. In conclusion, we demonstrate that the absence of CD36 alters whole-body vitamin A homeostasis and suggest that this phenotype is secondary to the impaired chylomicron metabolism previously reported in these mice.